IMPROVING EMPLOYEE SATISFACTION THROUGH DISCIPLINE AND TRAINING - Misransyah Akos; M Meliani (Jurnal Ekonomi dan Manajemen, 2020)
This study aims: (1) to know, test, and analyze the influence of work discipline on the employee satisfaction of UIN Antasari Banjarmasin; (2) to find out, test and analyze the effect of training on the employee satisfaction of educational staff in UIN Antasari Banjarmasin.The study applied descriptive quantitative method. The population of the study was Educational Staff with Civil Servants status in UIN Antasari Banjarmasin, with a total of 111 people. The sample was 63 people. The independent variable was work discipline and training while the dependent variable is employee satisfaction. Data collection was done by distributing questionnaires. Data analysis was using partial (Partial Least Square / PLS) regression analysis.The result of this study indicatedthat (1) work discipline had a positive and significant effect on employee satisfaction and (2) training had a positive but insignificant effect on employee satisfaction. Work discipline had a positive and significant effect on employee satisfaction of educational staff in UIN Antasari Banjarmasin. Training had a negative and insignificant effect on employee satisfaction of educational staff in UIN Antasari Banjarmasin.The higher ups must be more assertive and pay attention to the work discipline of the educational staff in UIN Antasari Banjarmasin to improve employee satisfaction so that they can work better, effectively, and efficiently